Stock identity of a humpback whale taken in a southeastern Caribbean hunt - Robbins , Jooke; Allen , Judith M.; Clapham , Phillip J.; Mattila , David K. (J. Cetacean Res. Manage., 2023)
North Atlantic humpback whales migrate annually between discrete high latitude feeding areas and shared low latitude breeding areas. St. Vincent and the Grenadines is a low density breeding area in the Lesser Antilles and the site of the only ongoing aboriginal humpback whale hunt in the North Atlantic. The Scientific Committee of the International Whaling Commission recently concluded that catches were likely drawn from a large, panmictic breeding population, but encouraged the collection of additional data. On 6 March 1999, two humpback whales were landed at St. Vincent and the Grenadines and we obtained images from an opportunistic source. Photographic matching identified one individual as ‘Haar’ (NAHWC #0694), a catalogued whale from the Gulf of Maine. This is the first stock assignment from this fishery and the most southeasterly sighting of a Gulf of Maine whale. Based on its reported length, the second animal was probably a calf and, if so, a member of the same population. This match provides further support for the hypothesis that catches at St. Vincent and the Grenadines involve a variety of high-latitude populations. Furthermore, it reinforces the scientific and management value of collecting and sharing individual identification data when hunts are performed.